A Fast and High-Precision Satellite-Ground Synchronization Technology in Satellite Beam Hopping Communication - Tengfei Hui; Shenghua Zhai; Zehui Zhang; Chong Liu; Xianfeng Gong; Zhitong Ni; Kai Yang (Space: Science & Technology)
A key requirement for future multibeam broadband satellite communication systems is the ability to flexibly adjust beam capacity according to changes in business distribution, in order to meet time-varying business requirements. Beam hopping technology provides an efficient solution to achieve the efficient use of frequency resources and power resources. At the same time, the use of beam hopping makes the beam hopping of satellite payload need to match the business signals of ground signal stations, bringing about the need for synchronization of beam hopping between satellite and ground. On the basis of analyzing the basic principles and key technologies of hopping beam, the paper analyzes the synchronization problem of satellite to ground hopping beam, proposes a signaling-assisted fast synchronization method of hopping beam for satellite to ground synchronization, and conducts simulation analysis of synchronization performance.